The influenza A (H1N1-2009) experience at the inaugural Asian Youth Games Singapore 2009: mass gathering during a developing pandemic. Issue 7 (2nd June 2010) - Lim, Hoon Chin; Cutter, Jeffery; Lim, Weng Kee; Ee, Adrian; Wong, Yoong Cheong; Tay, Boon Keng
Abstract : From 29 June to 7 July 2009, Singapore hosted the inaugural Asian Youth Games (AYG), which brought 1210 athletes and 810 officials from 43 participating countries. On 11 June, just 1 week before the Games Village Medical Centre started operations, the World Health Organization officially declared a global H1N1 2009 pandemic. Working in close partnership with the Olympic Council of Asia Medical Commission, Singapore AYG Organising Committee and other government agencies, the AYG Medical Services Committee was successful in preventing the local transmission of H1N1, which would have been a threat to the games, as it could have led to the cancellation of these games. This article describes the experience and valuable lessons learnt from managing a sports-related mass gathering during the developing pandemic.